2012
DOI: 10.1073/pnas.1210371110
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of Ezh2 by a small molecule inhibitor blocks tumor cells proliferation

Abstract: Ezh2 (Enhancer of zeste homolog 2) protein is the enzymatic component of the Polycomb repressive complex 2 (PRC2), which represses gene expression by methylating lysine 27 of histone H3 (H3K27) and regulates cell proliferation and differentiation during embryonic development. Recently, hot-spot mutations of Ezh2 were identified in diffused large B-cell lymphomas and follicular lymphomas. To investigate if tumor growth is dependent on the enzymatic activity of Ezh2, we developed a potent and selective small mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
415
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 503 publications
(436 citation statements)
references
References 40 publications
15
415
3
1
Order By: Relevance
“…15,[19][20][21][22][23][24] Notably, its molecular or pharmacological inhibition leads to the reversal of the malignant phenotype. [24][25][26][27][28][29] Collectively, these findings demonstrate a role of EZH2 as a potential prognostic marker and therapeutic target in cancer. We and others have recently reported that (i) as compared with the normal myoblasts and muscle tissues EZH2 is markedly overexpressed in RMS 30,31 and (ii) EZH2 downregulation in vitro leads to myogenic-like differentiation of an embryonal RMS cell line.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…15,[19][20][21][22][23][24] Notably, its molecular or pharmacological inhibition leads to the reversal of the malignant phenotype. [24][25][26][27][28][29] Collectively, these findings demonstrate a role of EZH2 as a potential prognostic marker and therapeutic target in cancer. We and others have recently reported that (i) as compared with the normal myoblasts and muscle tissues EZH2 is markedly overexpressed in RMS 30,31 and (ii) EZH2 downregulation in vitro leads to myogenic-like differentiation of an embryonal RMS cell line.…”
Section: Introductionmentioning
confidence: 72%
“…26,27,29 In the attempt to evaluate the effect of pharmacologic inhibition of EZH2, we have used DZNep, which has been already shown to induce FBXO32 expression in cancer cells 25,28,40,66 in parallel with an EZH2 catalytic inhibitor, MC1945. 33,34 Both pharmacological treatments phenocopied the effects of genetic inhibition of EZH2 in vitro enhancing the apoptotic rate of fusion-positive alveolar RMS cells, upregulating FBXO32 and downregulating Myogenin.…”
Section: (Student's T-test) (B) Ezh2mentioning
confidence: 99%
“…124 This compound reduced H3K27 trimethylation, which in turn resulted in apoptosis of mutant cancer cells with minimal effect on wild type cells. Wei Qi et al 125 reported the small molecule inhibitor of EZH2, El1, which also acts in a SAM-competitive manner and reduce H3K27me3 levels.…”
Section: Ezh2 As Potential Cancer Therapeutic Targetmentioning
confidence: 99%
“…Les molécules GSK126 et EI1 sont actives à la fois sur les deux formes d'EZH2. Elles inhibent de façon efficace la croissance de lignées cellulaires issues de lymphomes dans lesquelles la protéine EZH2 est mutée [41,42]. Une étude de phase I utilisant la molécule GSK126 a été lancée en avril 2014 chez des patients atteints de lymphomes B. Enfin, une autre étude clinique de phase I portant sur la molécule CPI-1205 dont la structure moléculaire n'a pas encore été dévoilée, a été initiée en 2015 chez des patients atteints de lymphomes B.…”
Section: Rôle Suppresseur De Tumeur D'ezh2unclassified